Financial Distress Analysis to Predict the Bankruptcy Rate of State-Owned Banks Using the Altman Z–Score Method - Hartomo, Bambang Widjanarko (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Bankruptcy is the inability of a company to continue its operations due to a decline in its financial condition and has liabilities or debts that are greater than the value of its assets. This study aims to predict the level of bankruptcy of state-owned banks using the Altman Z – Score method. Design/methodology/approach: This study uses a quantitative research approach with the Z – Score method. The data used is secondary data in the form of state-owned commercial bank financial reports for the period 2019 – 2021 which are listed on the Indonesia Stock Exchange (IDX), taken from the official website at www.idx.co.id. The variables used consist of 4 independent variables and 1 dependent variable, namely Working Capital to Total Assets (X1), Retained Earnings to Total Assets (X2), Earnings Before Interest and Taxes to Total Assets (X3) and Book Value of Equity to Book Values of Debt (X4) and analysis index Z – Score (Z). Findings: The results of the Z – Score calculation, the four banks in this study are in the Gray Area and Distress Area categories because working capital, retained earnings and operating profits are smaller than their total assets, and the amount of debt is greater than their total equity. The chance of bankruptcy will be even greater if the company's management does not immediately make improvements or evaluate the company's financial condition. Paper type: Research paper